Authenticity analyses of Phyllanthus amarus using barcoding coupled with HRM analysis to control its quality for medicinal plant product - Kittisak Buddhachat (2018)
© 2015 Elsevier B.V. The Phyllanthus genus, a plant used in traditional Thai medicine, has according to several pharmacopeias hepatoprotective properties. Not only is the anatomical morphology of these species relatively similar but they also share the Thai co mmon names Look-Tai-Bai which might cause confusion for laypersons. This study attempted to develop a method for accurate identification of Phyllanthus species, especially Phyllanthus amarus, and to detect contaminants in P. amarus products by using DNA barcoding coupled with high resolution melting (HRM) analysis (bar-HRM). Two plastid loci (rbcL and trnL) were chosen for DNA barcoding to generate a suitable primer for distinguishing Phyllanthus species by HRM analysis. The five species of Phyllanthus were subjected to amplification for testing the specificity and discrimination power of the designed primers derived from rbcL and trnL regions. Sensitivity of the method (DNA barcoding conjugated with HRM) to detect adulterant in P. amarus samples was evaluated. The commercial P. amarus products obtained from a local market were authenticated. The primer pair derived from trnL DNA barcoding (PhylltrnL) had more specificity and power of discrimination for Phyllanthus species than that derived from rbcL DNA barcoding (PhyllrbcL). The result showed that T m of P. amarus, Phyllanthus urinaria, Phyllanthus debilis, Phyllanthus airy-shawii, and Phyllanthus virgatus was 74.3 ± 0.08, 73.04 ± 0.07, 73.36 ± 0.05, 72.21 ± 0.06, 72.77 ± 0.15°C, respectively. This method proved to be a very sensitive tool that can be used for rapid detection of contamination as low as 1% of other Phyllanthus species in P. amarus admixtures. All commercial products of P. amarus obtained from a local market in Thailand were found to contain pure raw materials of P. amarus without any substitution or contamination. Our results indicated that the use of DNA barcoding coupled with HRM was an efficient molecular tool for correct species identification. This molecular tool provides a noteworthy benefit for quality control of medicinal plants and industry plants for pharmacological prospects.